The Algerian war and the military internationalization strategy of the Algerian cause 1954-1961 - sidali, ahmedmessoud (The Algerian Historical Journal, 2026)
This study is included in the approach between two strategic issues which had been a cornerstone of the evolutionary path of the Algerian Revolution, the political internationalism of the Algerian issue and its stakes at the diplomatic containment policy that France was exercising against the delegates of the editorial revolution at the level of international forums,which prevented the empowerment to bring the Algerian issue out of the duality of the French-Algerian struggle ; hence, by the rising tide of the Algerian Revolution in 1955 ,especially at the regional level the question of broadening the cycle of the military conflict in the Moroccan and Tunisian lands would evolve, by setting up a rear military bases for the revolution which later became receiving logistical and even human support from Chinese and Russian techs and experts who have trained the National Liberation Army unit's stationed on the Algerian eastern and western borders'. Their presence meant a real danger for the entire region, but not only the western camp (The United States of America) and the French government at that time, but even the leaders of the Algerian Revolution. That's why we thought we'd stand by at the stake and its challenges which faced by the revolution, using reports of the Interim Government and the National Council of the Algerian Revolution through their discussions about the same issue and their awareness of the extent of this strategy.